Conditions for uniformly convergence of expansions of continuous functions from Nikolskii classes in eigenfunction expansions of the Schrödinger operator on closed domain - Jamaludin, Nur Amalina; Ahatjonovich, Anvarjon Ahmedov (AIP Publishing LLC, 2014)
In this work, spectral expansions of the Schrödinger operator −Δ+q(y1,y2) with the singular potential from W12(Ω) are investigated. Using the asymptotical estimation of spectral function of Schrödinger operator on closed domain uniformly convergence of eigenfunction expansions of continuous functions from Nikolskii classes is proved. Properties of the continuous functions from Nikolskii classes are used.